Channel geometry optimization for vertical axis wind turbines in skyscrapers. Issue 2 (4th March 2018) - Kefi, Seifeddine; Joneja, Ajay; K.T. Tse, Tim; Li, Sunwei
ABSTRACT: The desire for sustainability and improved air quality has led architects to explore integrating vertical axis wind turbines (VAWT) in urban skyscrapers. However, the efficiency of such solutions is sensitive to the geometry of the wind channel. In this paper, we present a general technique for optimization of the wind channel geometry. Using parametric curves to define the profile of the channel, and by quantizing the location of the control points, we propose an experimental design approach to determine near-optimal channel geometry. The solution is further improved by interpolating the performance function so obtained via a statistical tool called kriging. The approach is tested by an experimental study, in which the parameters of the fluid dynamic model are determined by a series of wind tunnel tests. GRAPHICAL ABSTRACT: